Effects of two atypical neuroleptics, olanzapine and risperidone, on the function of the urinary bladder and the external urethral sphincter in anesthetized rats - Vera, Pedro L (BioMed Central, 2001)
BACKGROUND: A previous report showed that the atypical neuroleptic clozapine resulted in marked changes in urodynamic parameters and greatly inhibited the activity of the external urethral sphincter in anesthetized rats. Such findings may help explain the high incidence of urinary disturbances reported during clozapine therapy. In an effort to extend our observations to other atypical neuroleptic agents, the present study investigated the effects of two newer atypical antipsychotics, olanzapine and risperidone, on the bladder and external urethral sphincter during cystometry in anesthetized rats. RESULTS: At a dose of 0.1 mg/kg (i.v.), olanzapine decreased the micturition volume and increased the residual volume. In addition, olanzapine decreased the expulsion time and the amplitude of the high frequency oscillations observed during the expulsion phase. Larger doses (1 mg/kg) had a greater effect. Olanzapine also reduced the activity recorded from the external urethral sphincter, and the bursting observed during the expulsion phase was abolished by 1.0 mg/kg. Risperidone had similar effects although the maximal effects were smaller than those observed with olanzapine. The amplitude of bladder contractions elicited by electrical stimulation of the pelvic nerve was reduced by olanzapine but not risperidone suggesting a possible anti-muscarinic peripheral effect of olanzapine. CONCLUSIONS: Olanzapine and risperidone significantly altered several voiding parameters and decreased the activity of the external urethral sphincter in the anesthetized rat. We propose that these effects are due to the central action of these drugs and not to peripheral effects. These findings may explain some of the clinical reports of urinary incontinence with risperidone and may predict similar occurrences with olanzapine therapy.